NeMO analytics‐AD: The neuroscience multi‐omic visualization and analysis platform, now extended to support Alzheimer's disease: Development of new models and analysis methods/novel assays and technologies. (7th December 2020) - Chrysostomou, Elena; Prater, Katherine E.; Song, Yang; Orvis, Joshua; Kancherla, Jayaram; Herb, Brian; Ament, Seth; Bravo, Hector C.; Mahurkar, Anup A.; White, Owen; Garden, Gwenn A.; Hertzano, Ronna
Abstract: Background: Recent years have resulted in tremendous progress in understanding Alzheimer's disease via the generation and analysis of multi‐omic data. In addition, the BRAIN initiative has been mapping gene expression in the normal brain, which is important in understanding disease. However, a barrier for the broad usage of these data has been limited access and the requirement for informatics support to allow biologists not trained in programming to meaningfully access this wealth of information. Method: To address this challenge, we reveal, for the first time, an expansion of the Neuroscience Multi‐Omic (NeMO) Analysis and Visualization platform (NeMO Analytics, nemoanalytics.org) to include a focus on Alzheimer's Disease. NeMO Analytics gene expression tools are powered by gEAR (umgear.org) and consists of six components: (i) An expression browser, which allows the visualization of gene expression across datasets; (ii) A comparator tool for basic comparison of all of the genes in two groups; (iii) An elaborate single cell workbench; (iv) A dataset uploader, which allows seamless integration with the NeMO Archive data portal for data import, as well as import of user‐supplied datasets in a market exchange format (MEX); (v) A dataset curator that allows the user to define visualization preferences (e.g., data presentation as bar, line, x‐y scatter, violin plot, tSNE, or SVG); and (vi) A dataset manager, which allows the selection of groups of datasets to visualize side‐by‐side and manage dataset sharing. NeMO Analytics also allows the visualization of epigenetic data via integration of the Epiviz tool (https://epiviz.github.io/ ). Results: NeMO ‐AD provide biologists with meaningful access to a variety of datasets relevant to Alzheimer's research with data from different species, including human at different stages of the disease. Users can also create profiles (collections of datasets for visualization side‐by‐side) from additional data originating from the BRAIN initiative and deposited in the NeMO Archive or NeMO Analytics. Conclusion: The NeMO‐AD offers biologist unprecedented meaningful access to multi‐omic data relevant to Alzheimer's disease. We propose that broad usage of this platform to share and disseminate data will result in a unique and meaningful repository for biologists studying Alzheimer's disease.